The Role of Small Medium Enterprises in the implementation of Local Economic Development in South Africa - Nkwinika, M. K. K.; Munzhedzi, P. H. (SAAPAM (South African Association of Public Administration and Management), 2016)
The notion of Local Economic Development (LED) in local government is pivotal and continues to generate debates among policy-makers, civil society groups and scholars throughout the globe. This is particularly because the local sphere of government is responsible for provision of basic services. LED in local government debate stems among other challenges of unemployment, infrastructure backlog and access to funding. Consequently, there is consensus among all these stakeholders that LED may have consequences for the socioeconomic development programmes, particularly of developing countries including in rural provinces in South Africa. Small medium enterprises play a fundamental role in promoting LED. It is from this premise that this conceptual paper seeks to explore the role of small medium enterprises in LED. The paper further seeks to identify challenges associated with the contribution of small medium enterprises in economic development so as to recommend possible solutions to the identified challenges. It is concluded that amongst other challenges, the local sphere of government in the Limpopo Province lacks the necessary financial and human resource capacity to provide the said basic services and the requisite infrastructure.
Conference proceeding, Article
Keywords: Local Economic Development; Small Medium Enterprises; Corruption; Economic development -- South Africa; Local government -- South Africa; Small businesses